Artificial Skin Model simulating dry and moist in vivo human skin friction and deformation behaviour. (May 2016) - Nachman, M.; Franklin, S.E.
Abstract: In vivo friction and indentation deformation experiments were carried out using the human volar forearm of a healthy 29 year old Caucasian woman and compared with various synthetic materials in order to select materials and develop a new moisture-sensitive Artificial Skin Model (ASM). Analogous to human skin the final ASM comprised two different layers: a relatively stiff hydrophilic moisture-absorbing top layer representing the epidermis and a very soft under-layer representing the dermis and hypodermis. The friction and deformation behaviour of the new ASM were comparable to human skin when tested under dry and moist skin conditions. This development has potential for use as a test-bed in the development of devices that interact with the skin in a mechanical way. Highlights: A new composite 2-layer Artificial Skin Model for tribological behaviour is proposed. Analogous to human skin the top layer is moisture-absorbing. The friction and indentation behaviour mimics human skin in the dry and moist states. Intended use as a test-bed for devices that interact with skin on the human body.